2019
DOI: 10.1016/s2214-109x(19)30402-4
|View full text |Cite
|
Sign up to set email alerts
|

Call to action for equitable access to human milk for vulnerable infants

Abstract: Panel: Ethical considerations to shape key actions Ethical considerations VulnerabilityConsider potential medical, social, and economic vulnerabilities of both donor and recipient mother-infant dyad and mechanisms for reducing vulnerabilities. Equity and fairnessConsider which populations carry the risks and burdens of supplying donor human milk; and which receive the benefits of donor human milk. Consider how equity and fairness are addressed through allocation and access to donor milk and develop safeguards … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 8 publications
0
32
0
1
Order By: Relevance
“…Before the pandemic, the Oxford-PATH Human Milk Working Group emphasised the need to establish governance mechanisms and enact legislation for the safe and ethical use of DHM. 53 During the pandemic, a call to action by the Global Virtual Communication Network of Human Milk Banks and Associations concluded that milk banks are chronically under-resourced and deserve better protection in emergencies. 54 Unfortunately, implementation guidelines for human milk banks have not been endorsed by the World Health Assembly and few countries have Box 1 Case report of a woman with suspected COVID-19 giving birth to twins in Quang Ninh, Vietnam.…”
Section: Discussionmentioning
confidence: 99%
“…Before the pandemic, the Oxford-PATH Human Milk Working Group emphasised the need to establish governance mechanisms and enact legislation for the safe and ethical use of DHM. 53 During the pandemic, a call to action by the Global Virtual Communication Network of Human Milk Banks and Associations concluded that milk banks are chronically under-resourced and deserve better protection in emergencies. 54 Unfortunately, implementation guidelines for human milk banks have not been endorsed by the World Health Assembly and few countries have Box 1 Case report of a woman with suspected COVID-19 giving birth to twins in Quang Ninh, Vietnam.…”
Section: Discussionmentioning
confidence: 99%
“…Access to DHM is important in NICUs. If MOM cannot be given for some reason, DHM is the next best option and is always preferable to infant formula (Israel-Ballard et al, 2019). In Sweden, shortages of DHM sometimes occur, possibly due to its short shelf-life which makes it difficult to store large amounts.…”
Section: Introductionmentioning
confidence: 99%
“…2 This growth has led to calls for equitable access to human milk for vulnerable infants, such as low birthweight babies with necrotising enterocolitis. 3 Despite recommendations for donor human milk and the global expansion of human milk banks, little authoritative guidance exists on the implementation, operation, and regulation of human milk banks. The importance of safe operational guidelines and a coordinating body to collate and communicate data have been highlighted by the milkbanking community and emphasised by the current COVID-19 pandemic.…”
Section: Human Milk Banks: a Need For Further Evidence And Guidancementioning
confidence: 99%